(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2026)
Background: Gunshot head injuries are a major cause of death and illness, particularly in regions experiencing civil unrest. During the civil unrest in Bangladesh in 2024, violent crackdowns resulted in numerous gunshot injuries, many to the head. This study assesses the clinical features, surgical interventions, and outcomes of patients with gunshot head injuries during the civil unrest. Methods: This study at Bangabandhu Sheikh Mujib Medical University (currently Bangladesh Medical University), National Institute of Neurosciences, and two private hospitals in Dhaka (July 16–September 9, 2024) included 217 patients with gunshot head injuries. Data were collected from medical records and patient interviews. Injury characteristics, surgical interventions, post-operative complications, and functional outcomes (Glasgow Outcome Scale, GOS) at two months were analysed. Results: All patients were male, with the majority aged 14–25 years (80.2%), and most were students (70.5%). Low-velocity firearms caused 89.9% of injuries. Radiological findings showed scalp involvement in 76.5% of cases, parietal lobe injury in 8.3%, brain oedema in 71.9%, and haemorrhagic contusions in 46.5%. Surgical intervention was necessary for 54.8% of patients. Post-operative complications included brain oedema (30.4%), infection (9.7%), and hemiparesis (7.4%). A good recovery (GOS 5) was achieved in 76.5% of patients, 7.4% experienced moderate disability (GOS 4), and 16.1% died (GOS 1). Conclusion: Despite the high-risk nature of gunshot brain injuries, early intervention resulted in favourable functional outcomes. Rapid neurosurgical care, combined with intensive care support, significantly contributed to the high survival and recovery rates.